Karakteristik Kimia dan Organoleptik Rumput Laut (Eucheuma cottonii) Fermentasi dengan Perbedaan Lama Waktu Fermentasi dan Jenis Gula - Vhedila Carina Geraldine; Herpandi Herpandi; Rodiana Nopianti (Universitas Sriwijaya, 2015)
The purpose of this research was to determine the effect of different fermentation time and the type of sugar to the chemical, organoleptic characteristics of fermented seaweed and consumer acceptance level by looking at the level of preference for the product. The research method in this study used a factorial randomized block design (RAKF) with two treatments factor and repeated twice. The first factor was time ot the fermentation (W0 (zero hour), W1 (24 hours), W2 (48 hours) and W3 (72 hours)) and the second factor was the type sugar (G0 (without sugar), GP (sugar), GA (palm sugar) and GK (coconut sugar)). The parameters of observation were ash content, lactic acid, pH range, dietary fiber and organoleptic (appearance, color, odor, texture and taste). The results showed that the treatments difference of fermentation time dan sugar on the fermented seaweed product was significant for all the treatments. The best treatment based on chemical and sensory analysis were product with addition of sugar and 48 hours fermentation time.